2014
DOI: 10.1097/bot.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

No Contribution of Tension-Reducing Rotator Cuff Sutures on Locking Plate Fixation in a 2-Part Proximal Humerus Fracture Model

Abstract: Tension-relieving rotator cuff sutures added to locking plate fixation did not lead to a change in fracture gap with cyclic loading or an increase in ultimate failure load in a 2-part surgical neck proximal humerus fracture model without medial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The lack of consistency regarding the optimal fixation of 2-part PHFs with medial calcar disruption in elderly individuals in the literature, 15,16 accompanied by the debilitating nature of shoulder function, warrants further exploration into this challenging issue. We performed this retrospective study to assess outcomes of older patients sustaining 2-part PHFs with medial column disruption stabilized using this PHILOS plate plus oblique insertion of autologous fibula as a primary procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of consistency regarding the optimal fixation of 2-part PHFs with medial calcar disruption in elderly individuals in the literature, 15,16 accompanied by the debilitating nature of shoulder function, warrants further exploration into this challenging issue. We performed this retrospective study to assess outcomes of older patients sustaining 2-part PHFs with medial column disruption stabilized using this PHILOS plate plus oblique insertion of autologous fibula as a primary procedure.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, previous investigations evaluating the use of suture fixation into the rotator cuff in 2-part and 3-part proximal humerus fractures have concluded that there is no benefit to this practice. 8,9 In these studies, tuberosities remained attached to the head fragment or were part of a large cortical piece that was well secured by the plate and screw device, a situation that is uncommonly encountered in more complex fracture patterns where the tuberosity fragments are uncommonly so large. This discordance between recommended clinical practice and biomechanical data was an additional reason we sought to investigate the contribution of muscular forces on fracture alignment.…”
Section: Discussionmentioning
confidence: 99%
“…The interfragmentary displacements and rotations recorded from these systems can help locate regions of local instability within construct, especially in complex three-part fractures [ 57 , 61 , 82 , 84 ]. Also, fracture gap distance and the relative displacements and rotations between bone and implant can been calculated from these systems [ 64 , 69 , 85 87 ]. These two parameters have the advantage that they are both already measured in clinic to assess post-operative stability of bone-plate constructs [ 112 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same three muscles were loaded by Walsh et al [ 81 ] to represent glenohumeral abduction of 30°. Two studies [ 85 , 86 ] testing cadaveric tendons were based on the biomechanical study by Osterhoff et al [ 71 ]. Sinatra et al [ 85 ] used custom-made shoulder testing setup connected to a material testing machine to recreate 50–100° single plane shoulder abduction.…”
Section: Biomechanical Testing Of Proximal Humerus Platesmentioning
confidence: 99%
See 1 more Smart Citation